Analysis of "Bunga Gugur" by W. S. Rendra: A Semiotic Model of Literary Studies - Rois Abdul Haris; Sumiyadi Sumiyadi (Lakon : Jurnal Kajian Sastra dan Budaya, 2023)
This study examines the poem "Bunga Gugur" by W. S. Rendra which is part of a collection of poetic expressions for Dik Narti using a semiotic model. This scientific work aims to describe the results of a study of one of W.S. Rendra’s love poems during his lifetime. This study uses a semiotic model based on the sign system, how it works, how it is used, and what we do with it. The study of this semiotic model is divided into three stages including analysis of syntactic, semantic, and pragmatic aspects. A qualitative descriptive method was used in this study to describe the meaning of poetry so that readers can understand it as a unique literary work, having a sign system, message and meaning. The data source used is the primary data source in the form of the poem "Bunga Gugur". The secondary data sources are in the form of books and articles on literary studies, poetry, and semiotics. The results of the study found that the poem "Bunga Gugur" has conventional typography, which interprets the life of a loved one who has left this natural world. With the aim of expressing the author's heart to himself, so that the reader feels what the author feels.